2014
DOI: 10.1080/02678292.2014.919668
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical structure on the optical properties of new side-chain polymers containing cholesterol

Abstract: Poly[1-(cholesteryloxyhexyloxy)ethylene] (PHET) and poly [1-(cholesteryloxycarbonyl-hexyloxy)ethylene] (PHES) were prepared by reacting poly(vinyl alcohol) with cholesteryloxyhexyloxy bromides (CHB) or cholesteryloxycarbonylhexyloxy bromides (CEHB), and their thermal and optical properties were investigated. PHET and PHES exhibited monotropic cholesteric phases; however, their thermal behaviours depended on the cholesteryl groups and alkylene spacers with different chemical structures. PHET did not display ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, it does have an effect on the more flexible acrylic backbone where the LC behaviour is observed only upon passing a critical threshold of molecular weight of 12 × 10 3 gmol −1 . By switching the spacer from an ether (Figure 2A) to an equivalent ester, (Figure 2B) Yang et al demonstrated that the transition temperature to the N* mesophase shifted from −27 • C in the ether linker to 72 • C in the ester case whilst having little impact on the clearing temperature [34]. This switching of the spacer from an ether to an equivalent ester also caused the polymer to display crystallisation rather than a glass transition.…”
Section: Liquid Crystalline Polymers Bearing Sterol Side Groups Synth...mentioning
confidence: 98%
See 1 more Smart Citation
“…However, it does have an effect on the more flexible acrylic backbone where the LC behaviour is observed only upon passing a critical threshold of molecular weight of 12 × 10 3 gmol −1 . By switching the spacer from an ether (Figure 2A) to an equivalent ester, (Figure 2B) Yang et al demonstrated that the transition temperature to the N* mesophase shifted from −27 • C in the ether linker to 72 • C in the ester case whilst having little impact on the clearing temperature [34]. This switching of the spacer from an ether to an equivalent ester also caused the polymer to display crystallisation rather than a glass transition.…”
Section: Liquid Crystalline Polymers Bearing Sterol Side Groups Synth...mentioning
confidence: 98%
“…It does so by decoupling the mesogenic units and allowing them to freely form the mesophases. Both the type of the spacer and the length of the spacer are important [34]. Additionally, the stability and formation of the N* phase in polymers can be affected even by a small change in the chemical structure of the polymer.…”
Section: Liquid Crystalline Polymers Bearing Sterol Side Groups Synth...mentioning
confidence: 99%
“…Its eight chiral centres (carbon atoms) may, in principle, allow for 2 8 = 256 stereoisomers, however only one occurs in nature. Many cholesterol derivatives have cholesteric mesophases due to the presence of the cholesteryl residue in their molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, imidazolium-based ionic liquid crystals bearing a cholesteryl mesogenic group were synthesised and characterised [6], effects of chain branching and lateral fluorine substitution on mesomorphism of cholesteryl benzoates has been investigated [7], as well influence of chemical structure on the optical properties of new side-chain polymers containing cholesterol was identified. [8] Cholesterol-based dimeric liquid crystals have also been studied in terms of mesomorphic properties of their frustrated phases. [9] Cholesteryl benzoate derivatives, whose transition properties were reported in [10], were also found capable of forming cholesteric liquid crystal glasses.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the many LC compounds based on cholesterol or its derivatives have been reported to study optical-electric properties, thermochromism and circular dichroism. [31][32][33][34][35][36] Besides, LC materials containing cholesteryl groups have especially attracted more and more attention in the biomaterials fields. [3,[21][22][23][24][37][38][39][40][41] Stupp et al first reported the synthesis of cholesterol end functionalised oligo(L-lactic acid) and their interactions with cells.…”
Section: Introductionmentioning
confidence: 99%